Women, Society and Nation in Frances Sheridan’s The Memoirs of Miss Sidney Bidulph and Elizabeth Sheridan Le Fanu’s The Triumph of Prudence over Passion - Gallchoir, Clíona Ó (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The recent attribution to Elizabeth Sheridan Le Fanu of several novels published anonymously between 1780 and 1803 has significantly altered perceptions of the author, offering the potential to reconsider the relationship between her work and that of her mother, the celebrated novelist and dramatist Frances Sheridan. In this article, I explore the shared concerns with women’s role in social progress and improvement that link Frances Sheridan’s The Memoirs of Miss Sidney Bidulph and Elizabeth Sheridan’s The Triumph of Prudence over Passion. I argue specifically that Sidney Bidulph should be recognized as offering a sceptical appraisal of eighteenth-century England’s self-conception as a “polite nation” and the associated claims that this quality of politeness afforded English women the ability to influence their society for the better. The Triumph of Prudence over Passion, in contrast, published at the height of the Patriot movement in Ireland, links its celebration of Ireland’s nationhood to women’s active contribution as citizens. The article situates its discussion in the context of the need for greater attention to female literary traditions in Ireland, in which the literary canon has been overwhelmingly constructed in terms of a line of male succession.